Pengetahuan Masyarakat dalam Melakukan Rekonstruksi Rumah Tinggal Pasca Gempa di Kabupaten Donggala - Yusriah, A.R.; Fahirah, Fahirah (Civil Engineering Department, Tadulako University, 2021)
Earthquake is a natural event that can not be avoided resulting in the number of buildings damaged, building construction plays an important role in the development process in each area, in this case the knowledge of the community when rebuilding houses is very important to know. This study aims to identify people's knowledge in reconstructing residential houses after the earthquake. The method used in this study was by distributing questionnaires to the affected communities, especially in Marana Village as many as 80 families. Data analysis uses descriptive statistics, reliability tests, Relative Rank Index (RRI) and Spearman's Rho correlation. The results of the study that the dominant variable of the community in reconstructing residential houses know how to repair the bones on the walls of the RRI with a value of RRI of 0.820, know how to fix the bone in the column with the RRI value of 0.800, know the type of mixture for the column with the RRI value of 0.780, know the comparison of concrete mixture for the column with the RRI value of 0.760, know the good bones used for the column with the RRI value of 0.740. The relationship between the highest dominant variables is the behavior of the community in knowing how to repair the bone on the wall of the hoe correlated with whether the public knows how to repair the bones in the column, obtaining the highest value of 0.672 including the criteria of strong correlation.